Changing patterns of cardiovascular diseases and subtypes induced by kidney dysfunction among 25–64 years in China from 1992 to 2021 - Guoqiang Zeng; Hongliang Wang; Pinghui Cao; Jinyang Zhao; Lingyun Liu; Hui Guo (BMC Public Health)
Abstract Background Cardiovascular diseases (CVD) remain a significant global health burden, particularly in China, where kidney dysfunction (KD) is a key risk factor. This study analyzed trends in the burden of KD-induced CVD and subtypes among the working-age population (25–64 years) in China over the past 30 years and explored its association with age, period, and birth cohort. Methods This study extracted data from the Global Burden of Disease (GBD) 2021, focusing on deaths and disability-adjusted life years (DALYs) caused by KD-induced CVD and subtypes, including ischemic heart disease (IHD), stroke, and lower extremity peripheral artery disease (LEPAD) among 25–64 years globally and in China from 1992 to 2021. Trends in disease burden were described by calculating age-standardized mortality rates (ASMR) and age-standardized DALYs rates (ASDR). Additionally, an age-period-cohort (APC) model was employed to estimate the overall annual percentage change in mortality (net drift), the annual percentage change for specific age groups (local drift), the relative risks of period and cohort effects, and the age-specific rates adjusted for period bias (age effect). Results From 1992 to 2021, the number of deaths and DALYs caused by KD-induced IHD and LEPAD among 25–64 years globally and in China showed an upward trend, while the number caused by stroke decreased. However, the ASMR and ASDR demonstrated a declining trend, with the disease burden in China being lower than the global level. Notably, the ASMR for IHD and LEPAD in Chinese males showed an upward trend. The declines in ASMR and ASDR were more pronounced in females than in males. The net drift for CVD and subtypes showed a downward trend, with differing patterns between males and females. Mortality rates from stroke in males was increasingly affecting younger populations, while LEPAD was more prevalent in older individuals. Aside from male IHD, the relative risks for CVD and subtypes across cohort and period analyses showed a slight decline. Females exhibited higher relative risks in earlier periods, but their decline in both period and cohort analyses was faster than that of males. Mortality rates for IHD and stroke increased with age, with males exhibiting higher mortality rates across all age groups compared to females. Conclusion Our findings provide strong evidence that from 1992 to 2021, KD-induced CVD and subtypes still require attention among the working population in China. There were notable differences across subtypes, genders, and age groups, with males experiencing higher mortality rates and cohort-period risks than females. Our study highlights the need for China’s public health authorities to develop tailored guidelines targeting specific CVD subtypes, genders, and age groups to prevent the further escalation of the KD-induced CVD burden.